Three Lines Of Defense Sebagai Respon Atas Fraud dan Upaya Pencapaian Sustainable Development Goals Desa - Rhosalina Damayanti; Aprina Nugrahesthy Sulistya Hapsari (Jurnal Akademi Akuntansi, 2022)
The repeated occurrence of corruption at village level is not in line with the expectations of sustainable development starting from village. Internal control is the only hope in managing this fraud risk. Through descriptive qualitative methods with data processing through the data reduction, data presentation, and drawing conclusions, this study aims to explore the role of three lines of defense at village level as an effort to prevent fraud and make the Sustainable Development Goals Desa success. This research was conducted in Desa Tanjungsari, gave results that three control guards are still not optimal due to weak supervision and internal audit functions, lack of transparency and fairness to stakeholders. As a conclusion, this approach is not appropriate as an indicator of internal control in the village due to limited resources. This research is expected to be able to become an evaluation in village governance and enrich studies for further research.